Intramolecular alder-ene reaction of 2-methyl-4-(alkynyloxy)cyclohexa-2,5-dienones: catalyst-free access to hydrobenzofuran derivatives - Rai, Archana; Bajpai, Priyam; Kundu, Ananya I.; Vanka, Kumar; Das, Utpal (Organic Letters, 2026)
An atom-economical intramolecular Alder-ene reaction has been developed to construct hydrobenzofurans via the direct coupling of an allylic hydrogen atom to an alkyne. This transformation delivers hydrobenzofuran and hydroindole scaffolds in a single step, incorporating all atoms of the starting materials and exemplifying high atom economy. The synthesized products serve as versatile intermediates and exhibit notable reactivity toward further derivatization, as showcased through a range of transformations enabling rapid access to structurally diverse and complex molecules.